Elizabeth Bishop and translation - Machova, Mariana (Lexington Books, 2017)
"This book offers a discussion of Elizabeth Bishop's translations through close-readings of a selection of poems, with particular attention to the features that relate them to translation, and suggests that translation can be seen as a poetic principle that can be related to the poet's original works"--